141k views
3 votes
Simplify, using the distributive property and then combining like terms.

4m−3(2m+1)

2 Answers

5 votes

Answer:

4m−3(2m + 1)

= 4m - 3*2m - 3*1

= 4m - 6m - 3

= -2m - 3

Hope this helps!

:)

User Eric Pigeon
by
5.0k points
6 votes

Answer:

-2m - 3

Explanation:

Remember to follow PEMDAS. First, distribute -3 to all terms within the parenthesis:

-3(2m + 1) = (-3 * 2m) + (-3 * 1) = -6m + (-3)

4m - 6m - 3

Simplify. Combine like terms:

(4m - 6m) - 3

(-2m) - 3

-2m - 3 is your answer.

~

User SangamAngre
by
5.1k points